Going Local 2.0: How to Reform Development Agencies to Make Localized Aid More Than Talk - Ang, Yuen Yuen (Stanford Social Innovation Review, 2018)
More and more global aid agencies believe they should replace one-size -fits-all best practices with locally tailored solutions, but they mus t shift from just agreeing to “go local” to preparing development expe rts for the task by taking on three major problems with their internal practices.